2011
DOI: 10.1002/pip.1019
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in multi‐crystalline silicon solar cell efficiency via addition of luminescent material to EVA encapsulation layer

Abstract: This paper shows that an enhancement in the performance of commercial screen‐printed multi‐crystalline silicon photovoltaic modules can be achieved via luminescent down‐shifting of the incident light. Using fluorescent organic dyes dissolved in the pre‐existing poly‐ethylene vinyl acetate (EVA) encapsulation layer, an increase in the short‐wavelength external quantum efficiency of over 10% absolute, which results in 0.18% absolute higher efficiency, is reported. This approach offers the opportunity for prompt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(76 citation statements)
references
References 19 publications
3
72
0
1
Order By: Relevance
“…3 Theory: use of fluorescent dyes in silicone PV encapsulant Fluorescent dyes can be used to guide light to PV cells [10], and addition of small amounts of fluorescent dye to PV encapsulants offers a method of adding colour at minimal cost, with minimal change in PV efficiency [11]. Figure 2 shows light incident on a PV cell that is encapsulated in material containing Lumogen Red 300, fluorescent dye.…”
Section: Aimmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Theory: use of fluorescent dyes in silicone PV encapsulant Fluorescent dyes can be used to guide light to PV cells [10], and addition of small amounts of fluorescent dye to PV encapsulants offers a method of adding colour at minimal cost, with minimal change in PV efficiency [11]. Figure 2 shows light incident on a PV cell that is encapsulated in material containing Lumogen Red 300, fluorescent dye.…”
Section: Aimmentioning
confidence: 99%
“…Improvements in dye colour intensity and PV performance will be achieved through use of a PV encapsulant in which the Lumogen dyes retain their fluorescence properties. Sheets of EVA (ethylene vinyl acetate) can be used as a host for Lumogen dyes [11]. Encapsulation with EVA requires use of a PV lamination process to apply heat and pressure, but the kiln firing processes that were used to fix the glass paint onto the testpiece, warped the glass surface.…”
Section: Electricity Productionmentioning
confidence: 99%
“…Improvements in dye colour intensity and PV performance could be achieved through the use of a PV encapsulant in which the Lumogen dyes retain their fluorescence properties. Sheets of EVA can be used as a host for Lumogen dyes [20]. Encapsulation with EVA requires use of a PV lamination process to apply heat and pressure, but the kiln firing processes that were used to fix the glass paint onto the test piece warped the glass surface.…”
Section: Dye Fluorescencementioning
confidence: 99%
“…Although the addition of dyes to Sylgard 184 was unsuccessful in this instance, it has been demonstrated that the same dyes can enhance PV performance when used within dyed encapsulant that is applied over and around c-Si PV cells [20,21].…”
Section: Further Developmentsmentioning
confidence: 99%
See 1 more Smart Citation